An Affective Events Model of the Influence of the Physical Work Environment on Interpersonal Citizenship Behavior - Zoghbi Manrique de Lara, Pablo, (Colegio Oficial de Psicólogos de Madrid, 2020)
Based on the Affective Events Theory (AET), this paper proposes a model of how the level of organizational citizenship behavior (OCB) directed at individuals (peers) (OCB-I) declines to the extent that physical conditions in offices make employees experience crowding perceptions and privacy invasions from peers. We hypothesize that: 1) crowding perceptions and privacy invasions by peers are related to employees' feelings of relational conflict with peers; 2) relational conflict negatively relates to OCB-I; and 3) this decrease in OCB-I is mediated by the employee's person-organization fit (POF) and empathic concern. A direct path from crowding perceptions and privacy invasions to OCB-I is also postulated. Data were collected from 299 respondents working in open-plan offices at four IT-based companies in Tehran, Iran. Results found significant positive links of relational conflict to privacy invasion, crowding perceptions and OCB-I; and from privacy invasion to OCB-I. Furthermore, POF and empathic concern mediated the link between conflict and OCB-I. The findings suggest that managers can promote OCB-I by regulating not only the psychosocial conditions of the work environment, but also the physical conditions.